2014
DOI: 10.1097/id.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of 2 Resonance Frequency Measurement Devices

Abstract: Resonance frequency analysis systems in Osstell Mentor and Osstell ISQ show almost perfect reproducibility and repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Another widely used noninvasive analyzer, a resonance frequency analysis (RFA) device (Osstell ISQ, Integration Diagnostics AB, Gothenburg, Sweden), shows implant stability quotient (ISQ) values on the device's display. ISQ values constitute a near-linear mapping from the resonance frequency to a more clinically useful scale that ranges from 1 to 100 [3,4]. In clinical situations, an ISQ value greater than 70 is considered to indicate high implant stability for implant loading [5].…”
Section: Introductionmentioning
confidence: 99%
“…Another widely used noninvasive analyzer, a resonance frequency analysis (RFA) device (Osstell ISQ, Integration Diagnostics AB, Gothenburg, Sweden), shows implant stability quotient (ISQ) values on the device's display. ISQ values constitute a near-linear mapping from the resonance frequency to a more clinically useful scale that ranges from 1 to 100 [3,4]. In clinical situations, an ISQ value greater than 70 is considered to indicate high implant stability for implant loading [5].…”
Section: Introductionmentioning
confidence: 99%
“…Meredith introduced this technology in 1996, and it is amply demonstrated that is a useful device for impartially estimating the implant’s stability when the implant is placed or at any time during follow up. The literature shows that is a reliable and reproducible technology [ 6 , 7 , 8 ]. The RFA is performed by measuring the ISQ (implant stability quotient), ranging from 0 (no stability at all) to 100 (the highest value of stability that can be achieved) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was introduced by Meredith in 1996 and is an extensively used tool for an impartial estimation of implant stability at any phase of treatment or follow-up due to its high reliability and reproducibility. It enables the clinician to monitor the stability of the implant over time and analyse its evolution (6-8). The unit of measure of RFA is the implant stability quotient (ISQ), and its scale values can oscillate from 1 to 100.…”
Section: Introductionmentioning
confidence: 99%